Meiotic mapping of radiation-induced DNA repair mutations and aberrations in Aspergillus nidulans: special features and use of translocations - E. Käfer (Fungal Genetics Reports, 1994)
We recently described epistatic grouping of several new DNA repair genes and reported their location in the genetic map of Aspergillus (Fig. 1 in Käfer and Chae 1994 Curr. Genet. 25:223-232 and next report in this Newsletter). Some of the properties of the 10 mutations involved are listed in Table 1. Supporting mapping data are presented here which showed the following special features; unusual patterns of recombination which identified three types of radiation-induced aberrations; useful translocation breaks some of which link up fragments of the meiotic map and will provided new markers for a physical map of the long arm of chromosome VII; poorly-fertile mutants which in heterozygous crosses produced "twin" cleistothecia, partly selfed for the other normally self-sterile parent; aberration-free strains which produced consistent recombination frequencies without chiasma interference, possibly because they were practically isogenic.